2014
DOI: 10.1016/j.ihe.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Trade finance and Latin America's lost decade: The forgotten link

Abstract: a b s t r a c tThe Great recession has brought back to foreground the link between trade credit, international trade and economic growth. Scholars have recently found that the effects of the fall in trade finance are strong and accurately explain the recent fall in international trade. We argue that the lost decade that followed Latin America's debt crisis is a useful comparative benchmark to recognize the scope of impact on international trade stemming from a sharp decline in trade finance. The years that fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The increase in lending was also accompanied by an increase in trade finance and the role of export promotion agencies. See Wellons (1987) and Alvarez and Flores (2014)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in lending was also accompanied by an increase in trade finance and the role of export promotion agencies. See Wellons (1987) and Alvarez and Flores (2014)…”
mentioning
confidence: 99%
“…The increase in lending was also accompanied by an increase in trade finance and the role of export promotion agencies. SeeWellons (1987) andAlvarez and Flores (2014) 12 Other scholars to analyze the role of macroeconomic fundamentals in the path to the crisis includeFrieden (1987),Fernández (1983) andBarandiarán and Hernández (1999).13 Using a long-term perspective,Reinhart, Reinhart, and Trebesch (2016) have shown that, historically, commodity prices and capital outflows precede sovereign defaults.…”
mentioning
confidence: 99%